SIMULATOR FOR MANUAL SKILLS DEVELOPMENT OF SURGICAL INTERVENTIONS ON THE SKULL CEREBRAL SECTIO - A. A. Smirnov; V. V. Tatarkin; I. G. Zakhmatov; A. T. Marianovich; M. V. Andreevskaya; A. I. Nazmiev; Sh. Sh. Kudlakhmetov; V. A. Rybakov (Креативная хирургия и онкология)
One of the aim of higher education and additional professional education is to create a wide range of abilities and profoundly fixed practical skills without harm to patient’s health. That determines the interest to the development and implementation of various virtual simulators. However nowadays there is no simulation set capable to give the opportunity to practice the technique of surgical intervention performance on the cerebral section of the skull and the brain highly close to reality. That is why the chief aim of this work is create the simulator for manual surgical skills mastering on the cerebral section of the skull in a real topographic anatomical environment. Based on data of the physical and chemical properties of tissues and their simulating stuff a unique simulator was created. It includes the brain, made of Vaseline and paraffin mixture, the Dura mater and skin made of cotton fabric impregnated by silicone, the skull as a cast from protakril. At the stage of testing this unique simulator neurosurgeon experts pointed out the high level of the approximate reality of the tactile sensations of the craniotomy stages performance. The ellaborated model is successfully implemented and effectively used in the process of learning and control of mastering manual skills by students and medical interns at North-Western State Medical University named after I.I. Mechnikov, Saint-Petersburg, Russia.